Self-regulated Learning for Elementary School Students' Mathematics Learning Using Think Pair Share - Amelia Dwi Astuti (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2024)
Background: Students need Self-regulated learning to achieve maximum learning outcomes. In mathematics, students are often faced with challenges in solving complex problems or questions. So, in order for students to be able to face these challenges, students must have the motivation and strategy to solve them. This shows that students must have good Self-regulated Learning skills. The Think Pair Share learning model, can accommodate and have a positive influence on students' self-regulated learning. Aim: This research aims to find out how much difference the influence of the Think Pair Share learning model has on students' Self-regulated Learning in studying Mathematics. Method: This research is quantitative research. The population and sample size are 21 fourth-grade students in one of the state elementary schools in Palangkaraya. Sampling was carried out using a purposive sampling technique. The data collection instrument is a self-regulated learning scale questionnaire. The research conclusion analysis technique used in this research is the paired sample t-test. Results and Discussion: The SRL t_calculation value obtained using TPS learning was 7.074 and a significance value of 0.000. The significance value is 0.000 < 0.05 and t-count > t-table, namely 7.074 > 1.976 so Ho is rejected. Conclusion: There is a positive influence of Think Pair Share learning on the Self-regulated Learning of fourth-grade elementary school students in learning mathematics.